2019
DOI: 10.1021/acs.analchem.9b01038
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Cyclopropane Modifications in Bacterial Lipids via 213 nm Ultraviolet Photodissociation Mass Spectrometry

Abstract: Subtle structural features in bacterial lipids such as unsaturation elements can have vast biological implications. Cyclopropane rings have been correlated with tolerance to a number of adverse conditions in bacterial phospholipids. They have been shown to play a major role in Mycobacterium tuberculosis (M. tuberculosis or Mtb) pathogenesis as they occur in mycolic acids (MAs) in the mycobacterial cell. Traditional collisional activation methods allow elucidation of basic structural features of lipids but fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 80 publications
1
85
0
Order By: Relevance
“…Also, the most commonly used methods for the analysis of lipids in bacteria are thin-layer chromatography (TLC, reviewed by Fuchs [10]), gas chromatography (GC) [11,12], and nuclear magnetic resonance (NMR) [13,14], which offer limited information. Now, some methods based on mass spectrometry (MS) have been used for the detailed analysis of bacterial cell membranes lipidomics, including directly analyzing lipid extracts by matrix-assisted laser desorption ionization (MALDI) [15,16], liquid chromatography (LC) [17], and electrospray ionization (ESI) [16,18,19] coupled to MS. The introduction of UHPLC coupled to tandem MS (UHPLC-MS/MS) allows rapid and effective separation of individual lipid species and has been become a powerful tool for analyzing lipid classes in bacteria [20].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the most commonly used methods for the analysis of lipids in bacteria are thin-layer chromatography (TLC, reviewed by Fuchs [10]), gas chromatography (GC) [11,12], and nuclear magnetic resonance (NMR) [13,14], which offer limited information. Now, some methods based on mass spectrometry (MS) have been used for the detailed analysis of bacterial cell membranes lipidomics, including directly analyzing lipid extracts by matrix-assisted laser desorption ionization (MALDI) [15,16], liquid chromatography (LC) [17], and electrospray ionization (ESI) [16,18,19] coupled to MS. The introduction of UHPLC coupled to tandem MS (UHPLC-MS/MS) allows rapid and effective separation of individual lipid species and has been become a powerful tool for analyzing lipid classes in bacteria [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to product ions from the saccharide moieties of these compounds, diagnostic ions for FA side chains and the sphingoid base helped to extensively characterize the structure of these complex lipids. Follow-up studies showed that optimized experimental settings enable identification of DB positions [77,78], sn-isomers [77,79,80], hydroxylation sites as well as linkages [81], and FA branching/ cylclopropanation [82] sites in glycerophospholipids and sphingolipids when using 193 nm or 213 nm UVPD. All these studies showed that UVPD results in extensive metabolite and lipid fragmentation, thereby enabling annotation of structural details not accessible with CID methodologies.…”
Section: Photon-based Fragmentationmentioning
confidence: 99%
“…49 193 nm and 213 nm UVPD-MS/MS have been shown to facilitate near complete structural characterisation across multiple lipid categories and classes, including identification of positions of unsaturation via the observation of pairs of product ions formed by cleavage of allylic bond positions that differ in mass by 24 Da. [50][51][52][53][54][55][56][57][58][59][60] Sequential 'hybrid' MS n dissociation using HCD-MS/MS followed by UVPD-MS 3 has been shown to identify both unsaturation and sn-linkage positions in certain glycerophospholipids, [52][53][54] while most recently a reverse 'hybrid' UVPD-MS/MS and HCD-MS 3 approach has been shown to enable the improved structural characterisation of cholesterol lipids, including assignment of the cholesterol backbone, differentiation of isomeric of oxy-cholesterols, and localization of the site(s) of unsaturation within the acyl chains of cholesterol esters. 60 To date, however, UVPD-MS/MS or -MS n workflows have not been applied to FAHFA lipids.…”
Section: Introductionmentioning
confidence: 99%